Evaluation of the Physical and Mechanical Properties of Concrete with Steel Fibers from Recycled Tires for Applications in Coastal Areas - Escalante, Brus (2025)
This article addresses the low tensile strength in reinforced concrete structures affected by corrosion of reinforcing steel, as corrosion weakens the concrete by generating stresses that exceed its strength. Structures in coastal areas, such as Lima, are especially vulnerable due to the presence of chlorides and extreme weather conditions, which increase atmospheric corrosivity. The objective of this study is to evaluate the physical and mechanical properties of concrete enhanced with steel fibers obtained from recycled tires (RTSF) for applications in coastal areas. The characterization of the aggregates and the RTSF was carried out. In addition, a concrete mix design was developed with the addition of, 20kg/m3, 30kg/m3 and 40kg/m3 of RTSF. In addition, tests were carried out on the fresh concrete (slump, temperature and air content) and tests on the hardened concrete (tensile, compressive and flexural strength) to determine the workability, thermal control and the amount of air trapped in the mix, key factors for the durability and quality of the concrete. The analysis of the properties of RTSF shows that its incorporation improves various characteristics of the concrete, such as compressive and tensile strength, especially with 40 kg/m3 of fibers, which increase these strengths by 6.97% and 6.65%, respectively. An increase in the modulus of rupture is also observed, with the greatest increase in the 30 kg/m3 mix. However, the incorporation of RTSF increases the water absorption and porosity of the concrete, which can be a factor to consider in humid environments.